2008
DOI: 10.1111/j.1601-183x.2008.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Predator stress induces behavioral inhibition and amygdala somatostatin receptor 2 gene expression

Abstract: Psychological stressors precipitate and maintain stress-induced psychopathology, and it is likely that altered amygdala function underlies some of the deleterious effects of psychological stress. To understand the mechanisms underlying the linkage between the response to psychological stressors and maladaptive or psychopathological responses, we have focused on amygdala responsivity in animal models employing species-specific psychological stressors. In the present study, we characterized the effects of a 15-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 78 publications
5
35
0
Order By: Relevance
“…We found that 10% of the transcripts were differentially expressed (p ^ 0.01) between fish exposed to cues of a predator and a control group. These patterns are consistent with other studies involving predator cues [Nanda et al, 2008;Leder et al, 2009]. For example, a 15-min exposure to ferret olfactory, visual and acoustic cues increased stress-like behavior in rats and resulted in the differential expression of 7% of genes in the amygdala 3 h after exposure to a predator [Nanda et al, 2008].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…We found that 10% of the transcripts were differentially expressed (p ^ 0.01) between fish exposed to cues of a predator and a control group. These patterns are consistent with other studies involving predator cues [Nanda et al, 2008;Leder et al, 2009]. For example, a 15-min exposure to ferret olfactory, visual and acoustic cues increased stress-like behavior in rats and resulted in the differential expression of 7% of genes in the amygdala 3 h after exposure to a predator [Nanda et al, 2008].…”
Section: Discussionsupporting
confidence: 80%
“…This procedure elicited enduring changes in stickleback growth and behavior [Dingemanse et al, 2009;Bell et al, 2011], and other studies using this population have shown that they exhibit strong antipredator responses to rainbow trout [Bell and Sih, 2007]. Nanda et al [2008] used a similar procedure to measure the immediate brain transcriptomic response of rats to olfactory, visual and acoustic cues of predators. Sticklebacks were exposed to two types of olfactory cues.…”
Section: Applying Predator Cuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of this relative quantification can be found at http://docs.appliedbiosystems.com/pebiodocs/04303859.pdf. All quantifications were normalized to an established internal control for rodent brain (ribosomal S12 protein RNA, housekeeping gene), which was coamplified as described previously by others (Heinrich et al, 2006;Usarek et al, 2006;Nanda et al, 2008). For each group the results were given as mean 6 SEM.…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%